Optimal capacitor placement on West–East inter-tie in Saudi Arabia using genetic algorithm. (May 2018) - Shwehdi, M.H.; Mohamed, S. Raja; Devaraj, D.
Abstract: The growing demand for renewable energy resources, improved power factor, system stability, reliability and security is the target of Saudi Electricity Company (SEC); most of the loads are inductive and need more reactive power (VARs) thus adequate reactive power need to be provided. SEC has introduced the static voltage compensator (SVC) and capacitive banks to improve volt-ampere-reactive (VAR) power flow. Genetic approach (GA) is used to obtain the optimal data for load flow. This paper provides analysis of new-planned 380 kV West–East transmission line inter-tie networks performance under steady and transient states. It considers the reactive power compensation by the addition of capacitor bank at the terminals of the inter-tie. The GA method is outlined and implemented to dynamically solve the capacitor placement problem. The capacitor bank has improved power losses, operating voltage at different buses.